Empathetic perception level measured with the Jefferson scale in pediatric dentistry residents. - Quezada-Huerta, Betsi Luz (2020)
Objective: To determine the level of empathic perception measured with the Jefferson Scale among residents of the specialty of pediatric dentistry in the Cayetano Heredia University in Peru. Materials and methods: Cross-sectional, observational, descriptive study. The procedure was a survey of the level of empathy of postgraduate students with patients in the specialty of pediatric dentistry using the Jefferson Medical Empathy Scale. The statistical analyses were performed with the SPSS package version 24.0. Finally, bivariate tables were obtained considering the factors ofempathic perception according to gender, year of study, age, and type of patient admission. Results: The sample consisted of 34 postgraduate students of the specialty of pediatric dentistry of the University Cayetano Heredia in Peru. Empathic perception among the students was of medium level with 55.88% (n = 19). First year students presented an empathic perception of 60% (n = 6), being 54.17% in second year students (n = 13). In addition, there was a high level of empathy of 0% (n = 0) among males and 24.14% (n = 7) among females. There was a high level of empathy among 28 - 29-year-old students and in relation to the type of patient admission, while the perception of empathy was 66.67% (n=4) for CODIRO admissions and 53.57% (n=15) for regular admissions. Conclusions: While no significant differences were found in gender, year of study, or type of admission, there were differences in relation to the age of the students and the ability to “put oneself into another’s shoes”.